Upaya Tokoh Masyarakat Untuk Mencegah Perkawinan Anak Sebagai Bentuk Pendidikan Hukum - Eka Septi, Lia; Vien Permata H, Rima; Rejekiningsih, Triana (Universitas Ekasakti, 2023)
This research aims: To analyze the efforts of community leaders in preventing child marriage as a form of legal education in society. This research uses a form of qualitative research with a case study approach. Data sources were obtained from informants, places and events and documents. The main informants in this research are community figures, namely 1 religious leader and 1 marriage registrar. Supporting informants are children who carry out child marriages and parents of children who carry out child marriages. Data collection techniques include interviews with children who have child marriages, parents of children who have child marriages, community leaders (religious leaders and marriage registration officers), observations and documents. For data validity, source triangulation and technique triangulation were used. Meanwhile, the data analysis technique uses an interactive analysis model (Miles & Huberman 1984) which consists of data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the research, it can be concluded that the efforts of community leaders to prevent child marriage as a form of legal education include religious leaders providing education regarding the science of marriage at majlis ta'lim events and at marriage ceremonies, Marriage Registrar Officers only provide outreach to the community who will be carrying out the marriage. namely just before the contract takes place.